Ideais Primitivos e o Módulo Conormal - Junior., Reginaldo Amaral Cordeiro (2013)
In this work, our main objective is to introduce and investigate certain properties of the so-called primitive ideals of Pellikaan-Siersma, including a version relative to a pair of ideals and a generalization to higher order due to Jiang-Simis, as well as to apply such theory to the study of the conormal module M of an ideal in a quotient ring, with focus on an adequate description of its torsion part T(M) and on the freeness of the torsion-free module M=T (M). The connection between M and the second symbolic power of a certain ideal (the ideal whose conormal module is M) will also be highlighted.